Modification of Na+/H+ Exchanger in Human Platelets by 1,2-Dioctanoylglycerol, a Protein Kinase C Activator - Ozaki, Yukio; Mastsumoto, Yuki; Yatomi, Yutaka; Higashihara, Masaaki (Thrombosis and Haemostasis, 1990)
Protein kinase C activation in human platelets has a modulatory role in maintaining intracellular pH (pHi), by adjusting pHi at a particular value (7.22). Changes in pHi induced by protein kinase C appeared to be dependent upon the difference between H+ efflux catalyzed by the Na+/H+ exchanger and H+ production. The pHi recovery after acid loading was significantly facilitated by protein kinase C activation. Analysis of the rate constant for pHi recovery suggested that the turnover rate or the apparent affinity of the Na+/H+ exchanger for H+ was increased. Protein kinase C also decreased the Km value of the Na+/H+ exchanger for extracellular Na+. Thus, it is suggested that the role of protein kinase C in platelet pHi regulation is dual, adjusting the pHi value at a certain setpoint on the one hand, and increasing the rate constant of the Na+/H+ exchanger on the other.